AGE FEATURES OF FUNCTIONAL TRAINING FOR SWIMMERS IN MASTERS CATEGORY SWIMMERS SPECIALIZING AT 200 METERS FREE STYLE FOR MEN - Pirnazarov Sh.A. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. The article presents an analysis of the generalized sports results shown at the world championships in the Masters category at a distance of 200m freestyle for men. The aim of the study was to substantiate the approach to building a longterm training process among athletes in the Masters category, specializing in the 200m freestyle distance. As a result of the study, the age ranges were identified in which the use of training means aimed at developing and maintaining a high level of efficiency of anaerobic processes of energy supply of the body is relevant. It is recommended to build a long-term training process as follows. Until the age of 50, it is possible to include in the training process exercises aimed at developing and maintaining a high level of efficiency of anaerobic energy supply processes in the body, which will allow showing high results at medium distances. After 50 years, it is proposed to switch to performing at distances that require a lower proportion of the anaerobic component of the body’s energy supply, for example, to sprint or stayer distances.